Pelatihan Pembukuan Transaksi Keuangan Bagi Aparatur Desa - Samirah Dunakhir; Nur Afiah (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. This Community Partnership Program (PKM) aims to provide training as well as assistance for village officials in accounting for financial transactions. The partners of this activity are officials and employees of the Munte Village Government, Tanalili District, North Luwu Regency. Partner problems are: (1) limited knowledge in bookkeeping financial transactions, (2) there is an obligation for the Village Government to carry out financial administration and submit reports, and (3) limited human resources owned by the Village Government. The targets of this activity are village officials and Village Government employees who are able to book and record financial transactions. The methods used are: lectures, demonstrations, discussions, questions and answers, and partner assistance. The results achieved are (1) partners have knowledge in bookkeeping and recording of Village Government financial transactions, and (2) partners have the skills to compile Village Government financial reports in accordance with applicable Government Accounting Standards.